Healthy Lifestyle Behavior, Hardiness, and Psychological Distress in the Sandwich Generation - Stefanie Yovita Herawan; Arthur Huwae (Bisma The Journal of Counseling, 2025)
Approximately 56 million productive-age individuals in Indonesia are classified as the Sandwich Generation, facing psychological pressure due to their dual roles in caring for aging parents while raising children. This pressure may increase psychological distress, highlighting the need to understand protective factors that can mitigate its impact. This study aims to analyze the roles of healthy lifestyle and hardiness as predictors of psychological distress among Indonesia’s Sandwich Generation. The sample consisted of 432 respondents obtained through accidental sampling over a one-month period. A quantitative approach with multiple linear regression analysis was employed. The instruments used were the Health-Promoting Lifestyle Profile II (HPLP-II), Hardiness Scale, and Depression Anxiety Stress Scale (DASS-21). The results revealed that, simultaneously, healthy lifestyle and hardiness significantly predicted psychological distress. However, only hardiness emerged as a significant individual predictor. These findings emphasize the importance of psychological interventions that strengthen hardiness, with a healthy lifestyle serving as a supporting factor in reducing psychological distress among the Sandwich Generation.